The Etiology and Outcome of Upper Gastrointestinal Bleeding in Patients Presenting to Tertiary Care Hospital, Karachi - Syed Shayan Ali, Nazish Butt, Hafiz Haris Altaf, Amanullah Abbasi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study was to determine the causative factors that lead to bleeding in upper gastrointestinal tract and assess the outcomes after endoscopy. Methods: this study was conducted at the Department of Gastroenterology & Hepatology, JPMC, Karachi using a non-probability sampling technique and cross-sectional study design for the period of one year from October 2020 to September, 2021. Adult patients of age between 18 years to 60 years of both genders, presented either with upper GI bleeding were enrolled in this study. Baseline and clinical characteristics were collected in a structured questionnaire. After enrollment of patients, lower upper gastrointestinal and upper gastrointestinal endoscopy were performed to establish the diagnosis and source of bleeding and final analysis was performed using SPSS v. 23. Results: Five thirty-six patients with UGIB were recruited for final analysis and among them most common were males and accounted for 58.0% (n = 311) Large esophageal varices were was observed more prevalent cause of UGIB (57.4%, n = 308). Recurrent bleeding in 17 (5.6%) patients were observed under ≤50 years of age while 20 (8.6%) were of >50 years of age with a significant association between them (p= 0.028). Moreover, 02 (0.7%) died within 30 days under ≤50 years of age while 36 (15.5%) deaths were seen for those who were >50 years of age with a significant association (p< 0.001). Conclusion: In our study, we have observed that irrespective of age groups and gender, UGIB was most commonly caused by esophageal varices. Males were comparatively more prevalent. Our study also proves that risk of re-bleeding occurs as the age increasing along with higher short-term mortality. Keywords: Esophageal varices, UGIB, peptic ulcer, re-bleeding, mortality rate